The Middle East in the New Millenium - Feiler, Gil (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
This book is an in-depth portret of investment opportunity in the Middle East as it stands today. For each of sixteen countries, the author provides in-depth analysis of current economic, political, and business issues, with detailed attention to legislation in such vital areas as currency and banking, intellectual property rights, investment incentives, trade regulation, business form and structures, taxation, and the laws applicable to labor and environmental issues, as well as a desciption of relevant judicial procedures. The Middle East in the New Millenium represents the clearest indication we have yet of the prospects for crystallization of this region and the likely pace and aspect of economic liberalization.